1978
DOI: 10.1007/bf00349810
|View full text |Cite
|
Sign up to set email alerts
|

The effects of water- and nitrogen-induced stresses on plant community structure in a semiarid grassland

Abstract: A replicated factorial experiment was designed to test the hypothesis that manipulating inputs of water and mineral nitrogen to a semiarid grassland would disrupt existing interactions resulting in alteration of the structure of the primary producer community. Alteration of community structure was measured as either changes in growing season average biomass of 6 functional groups of plants or their relative contribution to total biomass.Additions of water greatly increased total biomass and resulted in the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
155
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(163 citation statements)
references
References 14 publications
5
155
3
Order By: Relevance
“…Losses in species richness were mainly due to decreases in perennial forbs while no significant changes occurred in annuals, shrubs and semi-shrubs, or annual forbs in our steppe (Song et al, 2011). This is in accordance with Lauenroth et al (1978) who found that changes in community structure occurred mainly in several dominant groups. Different species responses to N addition may also be related to species functional traits such as root depth, N use efficiency, and mycorrhizal colonization which are associated with strategies for species adaptation to variable nutrient conditions (Ren et al, 2011).…”
Section: Plantsupporting
confidence: 93%
“…Losses in species richness were mainly due to decreases in perennial forbs while no significant changes occurred in annuals, shrubs and semi-shrubs, or annual forbs in our steppe (Song et al, 2011). This is in accordance with Lauenroth et al (1978) who found that changes in community structure occurred mainly in several dominant groups. Different species responses to N addition may also be related to species functional traits such as root depth, N use efficiency, and mycorrhizal colonization which are associated with strategies for species adaptation to variable nutrient conditions (Ren et al, 2011).…”
Section: Plantsupporting
confidence: 93%
“…Control, water, nitrogen, and water-plus-nitrogen treatments were initiated in 1971 (Lauenroth et al 1978, Dodd andLauenroth 1979). The experimental design consisted of two replications of factorial combinations of water and nitrogen, with each treatmentreplicate extending over a 1-ha area, and the treatments applied from 1971 to 1975.…”
Section: Methodsmentioning
confidence: 99%
“…Treatments were terminated in 1975, after 5 yr, and vegetation was sampled through 1977 (Lauenroth et al 1978, Dodd andLauenroth 1979). Sampling was resumed in 1982 by sampling 10 permanent plots on each of five transects in each of the treatment-replicates (4 treatments X 2 locations X 50 plots).…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen (N) and water availability both directly control the functioning of arid ecosystems (Lauenroth et al 1978, Yahdjian et al 2011). In addition, water and N availability interact with each other so that water availability affects the N cycle; and N availability affects the water cycle.…”
Section: Introductionmentioning
confidence: 99%